Advances in cell therapy: progress and challenges in hematological and solid tumors - D'Avanzo, Claudia; Blaeschke, Franziska; Lysandrou, Memnon; Ingelfinger, Florian; Zeiser, Robert (Trends in pharmacological sciences, 2024)
Cell-based therapies harness the endogenous ability of the immune system to fight cancer and have shown promising results in the treatment of hematological malignancies. However, their clinical application beyond B cell malignancies is hampered by numerous hurdles, ranging from relapsed disease to a hostile tumor microenvironment (TME). Recent advances in cell engineering and TME modulation may expand the applicability of these therapies to a wider range of cancers, creating new treatment possibilities. Breakthroughs in advanced gene editing and sophisticated cell engineering, have also provided promising solutions to longstanding challenges. In this review, we examine the challenges and future directions of the most prominent cell-based therapies, including chimeric antigen receptor (CAR)-T cells, tumor-infiltrating lymphocytes (TILs), and natural killer (NK) cells, and emerging modalities. We provide a comprehensive analysis of emerging cell types and combination strategies translated into clinical trials, offering insights into the next generation of cell-based cancer treatments